Increasing Children's Vegetable Consumption: Translating a Review of the Evidence Base to Develop Best Practice Guidelines - Gilly A. Hendrie, PhD; Kim Anastasiou, PhD; Emily Brindal, PhD; Bonnie Wiggins, MMktg; Danielle L. Baird, BNutrDiet (Hons); Brittany J. Johnson, PhD; Lucinda K. Bell, PhD; Claire Gardner, MNutrDiet; Jennifer C. Arguelles, BNutrDiet; Amber Kelaart, MHSM; David N. Cox, PhD; Rebecca K. Golley, PhD (Elsevier, 2024)
Introduction: Dietary guidelines worldwide emphasize the importance of consuming vegetables as part of a healthy diet. Despite this, translating this information into messages for consumers that change behavior has been difficult. There have been population-level social marketing campaigns as well as several smaller campaigns directed specifically toward children, which have demonstrated small increases in consumption. However, achieving meaningful and sustained increases in children's vegetable consumption remains a challenge. This article describes the process of synthesizing the published literature and translating these findings to inform the development of 7 best practice guidelines to increase children's vegetable intake. Methods: The first step in this process was a systematic review of scientific literature to identify the components of interventions that were associated with successfully increasing vegetable intake. The synthesis of effective intervention components was guided by the Behavior Change Wheel. These scientific findings were translated to guidelines for best practice. This process involved a team of nutrition and behavioral researchers and nutrition practitioners translating the science into actionable advice that could be adopted by a range of stakeholders. The 6 selected stakeholders included long daycare centers, after-hours school care providers, primary schools, industry groups and growers, researchers, and government policy makers. Stakeholders were involved in the development process through surveys and interviews to understand their requirements for resources to support adoption of the best practice guidelines within each setting and within the context of existing practice. Results: The guidelines center on coordination of effort, with a focus on components such as planning, environmental restructuring, barrier reduction, feedback, and monitoring. In consultation with key stakeholders, a range of resources were developed for each setting to support the implementation of best practice, with the aim of achieving meaningful increases in intake. The resources and tools have been made available at http://www.vegkit.com.au. Conclusions: The translation of knowledge into practice is not traditionally included as part of the research process. Therefore, combining the process of reviewing the science and translating the evidence to stakeholder resources to influence practice in 1 research study is novel, and the study could be used to guide future research translation activities within and beyond the field of public health nutrition.